Functional Status of the Elderly and their Rehabilitation Needs: A Mixed-Method Study in a Slum of Kolkata, West Bengal - Riya Halder; Bobby Paul; Ankush Banerjee; Ranjan Das; Trina Sengupta (Siriraj Medical Journal, 2023)
Objective: A comprehensive understanding of the requirements of elderly is necessary to preserve their “functional capacity”, an important indicator of their health status. This study aimed to assess the functional status of the elderly and their rehabilitation needs. Materials and Methods: A mixed-method study was conducted from November 2021 to June 2022 at a health centre in Chetla, West Bengal, India. Quantitative data, collected from 172 elderly persons using a pretested questionnaire, were analyzed by logistic regression analysis. Qualitative data, collected via focus group discussions, were analyzed thematically. Results: Overall, 11.62% and 66.86% participants were functionally dependent in one or more activities of daily living (ADL) and instrumental activities of daily living (IADL), respectively. Significant association of age ≥70 years (AOR = 4.06, 95% CI= 1.13-14.63), male gender (AOR= 5.21, 95% CI= 1.57-17.28) and assistive device use (AOR= 6.92, 95% CI= 1.85-25.83) was found with ADL limitations. Increasing age (AOR= 1.29, 95% CI= 1.13-1.50), female gender (AOR= 13.97, 95%CI= 3.61-54.00), residence in joint family (AOR= 3.95, 95%CI=1.47-10.61), without spouse (AOR= 3.59, 95% CI= 1.12-11.44) and daily intake of multiple medications (AOR= 4.99, 95%CI= 1.45- 17.13) were factors significantly associated with IADL limitations. Major identified needs of the elderly were related to development of peer support groups, transportation systems and delivery of services from the health system. Conclusion: Rehabilitative services like providing assistive devices to the needy, developing elderly support groups, undertaking household visits for bedridden and those with restricted mobility, and building supportive environments within families and communities should be ensured.